Tax Consequences for Polish Businesses Upon Russia's Inclusion On the Eu Tax Haven List - Dawid GARSTECKI (Communications of International Proceedings, 2023)
The main motive of this article was the inclusion of the Russian Federation on February 14, 2023, in the EU list of non-cooperative jurisdictions for tax purposes in context of tax implications for Polish companies conducting business in Russian Federation. Polish tax regulations do not define tax havens, but they impose sanctions on Polish tax residents in connection with conducting business transactions with entities based in tax havens. These sanctions apply to both the EU tax haven list and the national tax haven list. The main objective of this study was to determine which areas of corporate income tax (CIT) are affected by the sanctions resulting from Russia's inclusion on the EU tax haven list. This primary goal was achieved through the analysis of legal acts, relevant literature, and deductive methods. The analysis revealed that the EU tax haven list impacts five areas of CIT: provisions regarding tax schemes, provisions on holding companies, provisions on controlled foreign corporations (CFCs), provisions on the disclosure of tax strategy information to the public and provisions on withholding tax. Then, an original division of sanctions in these areas into two types - economic and documentary - was made. Finally, a demand was formulated to the legislator regarding the inclusion of the Russian Federation on the national list of tax havens, as the current national tax regulations are not fully consistent (partly referring to the EU list and partly to the national list), causing confusion and doubts among Polish taxpayers.
Keywords: Tax law; tax regulations; tax havens.